Effectiveness of Big Clock Media in Teaching Analog Clock to Grade 1 Elementary School Students - Muhtaj, Mughnil; Alviansyah, David; Nailah, Faiqatun; Murtiyani, Tri; Kurnianto, Wirayoga Abdillah; Kurniawan, Yudi (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2025)
This study aims to measure the effectiveness of using big clock media in improving grade 1 elementary students' understanding of the concept of reading analog clocks. The research method used is a quantitative method with a pretest-posttest design to compare the results of students' initial and final tests after learning using large clock media. This research was conducted at SDN Pabian 4, with five students as samples. The results showed an increase in students' understanding of analog clock reading material, as indicated by the increase in the average score from the initial test of 36% to 84% in the final test. This finding emphasizes the importance of using concrete media in learning mathematics, especially for abstract materials. This research is expected to encourage further innovation in the development of creative and applicable educational media, as well as provide insight for educators in optimizing the teaching and learning process.